O espírito do doutor palhaço : palhaçoterapia e produção de saber em espiritualidade e humanização em saúde - Marinho, Allan Denizard Mota (2015)
The National Health Humanization Policy, since its creation in 2003, has been the target of intensive debates over its implementation in the routine of healthcare services. The Projeto Y de Riso, Sorriso e Saúde is a clowntherapy group of the Universidade Federal do Ceará that has been working for the past ten years towards the practice of a more humanized interaction with the hospitalized patient. The spirituality, with the notions of its field, is revealed in the praxis of these subjects beyond the philosophies of dialogue. This research, then, assumed, as its main objective, to comprehend the knowledge production in spirituality and humanization of assistance, trying to reveal the quality and the intensity of the relationships produced by this art in the hospital context. The methodology utilized was the collaborative-research, according to Ibiapina (2008), triangulated with the dense description of ethnography, elements of biografization, reflexive interviews and the utilization of bricolages – as this method suggests to do so to enrich the approach – that allowed a better manifestation of the participants. The author made a participant-observation, been present at the group’s reunions and living the clown’s visit at the hospital. The analysis of the speech recorded and transcripted, as well as the written material about the experiences of the group revealed categories that emerged from the meeting between the life of the under graduation students and the experience with the doctor clown: the self-knowledge stimulated by the clown’s mask, the child within and the other child, the monster-clown and monster-doctor. The dialogue with several authors, mainly with Henri Bergson and his neospiritualism, concluded how much the laughter activity for the improvement of the ill people enrich the cosmovision of the health apprentice, guiding him from the science of disease to the art of care. The ubiquitous presence of spirituality in this work exemplifies how this theme can be experienced at the various care practices with the humanization of assistance, pointing new dialogues that aggrandize the policy that governs this area.